Freedom to Learn from Ki Hadjar Dewantara's Perspective and its Relevance for the Development of Character Education - Jamil, Jumrah; M.Dun, Alyyuddin; Sahrun, Sahrun; Marhali, Rohani Dg; Joni, Juliati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to investigate and assess policy formulation. The concept of